Implementasi Branding dan Laporan Keuangan pada Usaha Opak Sari Rasa Indah dan Dapur Emak di Desa Citaleus - Farman, Fanji (Civiliza Publishing, 2024)
This research explains the community service program, especially for Opak Sari Rasa Indah and Dapur Emak MSME actors in KKN-T (Real Work Lectures - Thematic) activities in 2024 in Citaleus Village, Buahdua District, Sumedang Regency. The methods used are observation, interviews, documentation and socialization. The analysis carried out focuses on problems in terms of introducing Opak Sari Rasa Indah and Dapur Emak UMKM to the community as well as preparing simple financial reports. This analysis resulted in solving the problem in the form of a program that we implemented, namely creating a logo, banner, menu book, simple financial report application in the form of an application given to UMKM Opak Sari Rasa Indah and Dapur Emak. It is hoped that this problem solving method can help resolve the problems that exist among UMKM.